Society Exchange Characteristics, Service Quality, and Relationship Quality between Hospital and Its Suppliers - Te-Hsiu Sun; Chun-Yuan Cheng; Cheng min Chao (International Journal of Supply Chain Management, 2020)
Successful supply chain management provides an enterprise with a new competitive advantage. However, successful supply chain performance is based on a high level of trust and strong commitment among supply chain partners. Studies have indicated that communication, partner’s reputation, perceived benefits, fairness, and relationship tenure that are within the context of social exchange theory have an effect on trust. In the current study, we attempted to integrate two types of theories of social exchange and service quality by proposing an integrated model that influences the factor to trust and commitment. We then applied structural equation modeling to test the model. The study results indicated that a hospital’s trust in its supply chain partner is highly associated with commitment. The study included respondents comprising medical device procurement staff working in hospitals within Taiwan. A total of 500 questionnaires were distributed; 316 completed questionnaires were received. The results revealed that communication, partner’s reputation, and perceived benefits had a positive effect on trust. Service quality was also determined to have a positive effect on trust and commitment. This result should provide reference for a hospital and its relationship with suppliers, which helps monitor decision variables in the supply chain management of medical devices.